Lifestyle, cardiovascular risk knowledge and patient counselling among selected sub-Saharan African family physicians and trainees - Pius O. Ameh; Kenneth Yakubu; Miriam Miima; Olugbemi Popoola; Gulnaz Mohamoud; Klaus B. von Pressentin (AOSIS, 2019)
Background: Cardiovascular disease (CVD)-related deaths in sub-Saharan Africa (SSA) are on the rise, and primary care physicians could facilitate the reversal of this trend through treatment and prevention strategies. Aim: The aim of this study was to determine the relationship between physician lifestyle practices, CVD prevention knowledge and patient CVD counselling practices among family physicians (FPs) and family medicine (FM) trainees affiliated to FM colleges and organisations in SSA. Setting: FPs and FM trainees affiliated to FM colleges and organisations in Anglophone SSA. Methods: A web-based cross-sectional analytical study was conducted using validated, self-administered questionnaires. Following collation of responses, the relationship between the participants' CVD prevention knowledge, lifestyle practices and CVD counselling rates was assessed. Results: Of the 174 participants (53% response rate), 83% were married, 51% were females and the mean age was 39.2 (standard deviation [SD] 7.6) years. Most of the participants responded accurately to the CVD prevention knowledge items, but few had accurate responses on prioritising care by 10-year risk. Most participants had less than optimal lifestyle practices except for smoking, vegetable or fruit ingestion and sleep habits. Most participants (65%) usually counselled patients on nutrition, but less frequently on weight management, exercise, smoking and alcohol. The region of practice and physicians with poor lifestyle were predictive of patient counselling rates. Conclusion: Training on patient counselling and self-awareness for CVD prevention may influence patient counselling practice. Promoting quality training on patient counselling among FPs as well as a healthy self-awareness for CVD prevention is thus needed. The complex relationship between physician lifestyle and patient counselling warrants further study.